Researching a Rigged Game: Digital Approaches to Tracing the Illicit Trade in Cultural Objects - Emiline Smith; Summer Austin (Springer Nature Switzerland, 2025)
This open access book on open-source data and the trade in cultural heritage is foundational for object biography, provenance research studies, and social science methodological education. Interest in studying the (illicit) trade in cultural objects, as well questions around ownership, access and protection, have grown in recent years. However, this interdisciplinary field requires a range of methodological skills in order to trace an object's ownership history and the social network underpinning its trade. Drawing from a diverse group of researchers and practitioners, this edited volume brings together methodological, ethical and disciplinary considerations in the use of open source data to research the trade and transfer of cultural objects. As such, it will serve as the paramount guide to anyone who is interested in doing research on this topic.